Thematic Categorization of Cultural Analysis: A Proposal for Translation - Igareda, Paula (Íkala, Revista de Lenguaje y Cultura, 2011)
In this paper, an analysis is made of the cultural referents of several literary texts and their translation from Spanish into German and English using a methodological tool for cultural analysis. A brief overview is presented, first of the state of the art in relation to the translation of cultural elements, then of the main existing classifications and theories in order to structure the tool, and finally, some examples of how the cultural elements have been translated in the corpus of the study are described. One of the main conclusions is that translators favor the use neutralization or they look for a functional equivalent in the translation of this kind of works.